2015
DOI: 10.1007/s00415-015-7687-6
|View full text |Cite
|
Sign up to set email alerts
|

On visual hallucinations and cortical networks: a trans-diagnostic review

Abstract: Our current clinical approach to visual hallucinations is largely derived from work carried out by Georges de Morsier in the 1930s. Now, almost a century after his influential papers, we have the research tools to further explore the ideas he put forward. In this review, we address de Morsier’s proposal that visual hallucinations in all clinical conditions have a similar neurological mechanism by comparing structural imaging studies of susceptibility to visual hallucinations in Parkinson’s disease, Alzheimer’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 51 publications
1
33
0
Order By: Relevance
“…This literature points to cortical abnormalities in PDP, such as reduced gray matter volume in the hippocampus and in frontal, parietal, and occipital cortices (6), and to the presence of Lewy bodies in frontal, cingulate, temporal, and occipital cortices on postmortem examination (9). Psychotic symptoms in PD are often comorbid with dementia and, in some cases, may presage incipient dementia (82).…”
Section: Discussionmentioning
confidence: 99%
“…This literature points to cortical abnormalities in PDP, such as reduced gray matter volume in the hippocampus and in frontal, parietal, and occipital cortices (6), and to the presence of Lewy bodies in frontal, cingulate, temporal, and occipital cortices on postmortem examination (9). Psychotic symptoms in PD are often comorbid with dementia and, in some cases, may presage incipient dementia (82).…”
Section: Discussionmentioning
confidence: 99%
“…Despite methodological differences, structural imaging studies of visual hallucinations have yielded a number of consistent findings 98100 . Several studies have reported atrophy in the visual cortex 101103 — broadly defined as extending into lateral and ventral occipitotemporal regions including the fusiform gyrus and visual parietal cortex (corresponding to dorsal and ventral visual streams) — although this finding is not univeral 104 .…”
Section: Imaging and Electrophysiologymentioning
confidence: 99%
“…The lack of prominent deficits in other cognitive domains may reflect the small number of patients with formed hallucinations and differences in tests used in PPMI compared with previous studies of visual hallucinations. The deficits of visual and cognitive function in PD patients with visual hallucinations are thought to relate to volume loss in frontal, parietal, limbic, occipital and hippocampal cortex (see refs [32][33][34] for recent reviews). Here, we found evidence for these structural changes in patients with de novo PD who go on to develop formed hallucinations.…”
Section: Cognition Cortical Changes and Visual Hallucinationsmentioning
confidence: 99%